Complete Dissociation of Motor Neuron Death from Motor Dysfunction by Bax Deletion in a Mouse Model of ALS - Gould, Thomas W. (J Neurosci, 2006)
The death of cranial and spinal motoneurons (MNs) is believed to be an essential component of the pathogenesis of amyotrophic lateral sclerosis (ALS). We tested this hypothesis by crossing Bax-deficient mice with mice expressing mutant superoxide dismutase 1 (SOD1), a transgenic model of familial ALS. Although Bax deletion failed to prevent neuromuscular denervation and mitochondrial vacuolization, MNs were completely rescued from mutant SOD1-mediated death. However, Bax deficiency extended lifespan and delayed the onset of motor dysfunction of SOD1 mutants, suggesting that Bax acts via a mechanism distinct from cell death activation. Consistent with this idea, Bax elimination delayed the onset of neuromuscular denervation, which began long before the activation of cell death proteins in SOD1 mutants. Additionally, we show that denervation preceded accumulation of mutant SOD1 within MNs and astrogliosis in the spinal cord, which are also both delayed in Bax-deficient SOD1 mutants. Interestingly, MNs exhibited mitochondrial abnormalities at the innervated neuromuscular junction at the onset of neuromuscular denervation. Additionally, both MN presynaptic terminals and terminal Schwann cells expressed high levels of mutant SOD1 before MNs withdrew their axons. Together, these data support the idea that clinical symptoms in the SOD1 G93A model of ALS result specifically from damage to the distal motor axon and not from activation of the death pathway, and cast doubt on the utility of anti-apoptotic therapies to combat ALS. Furthermore, they suggest a novel, cell death-independent role for Bax in facilitating mutant SOD1-mediated motor denervation.